Peningkatan Hasil Belajar Matematika Menggunakan Pendekatan Realistic Mathematic Education Materi Pecahan Kelas II-A SDN Manukan Kulon Surabaya - Durrotun Nafila; Mintohari Mintohari; Ana Sofiya (Departement of Mathematics Education, 2023)
The general objective of this classroom action research is to develop students' abilities to actively participate in mathematics learning between students and teachers, by using realistic approach techniques to improve students' mathematics results or achievement. Using realistic techniques, this classroom action research was conducted over two time periods. Planning, activities, observation, and reflective analysis form four phases in each cycle. To discuss a series of work, and the final test of the cycle each student gathers with other group members. The results of classroom action research are: (1) student achievement has increased compared to before; (2) cycle I only had 72.42% willingness to learn; and (3) cycle II needs corrective action. Based on the observation results of the second cycle, it increased to 96.55%. According to this research, learning mathematics will be more effective if students take a realistic approach to each subject matter, so teachers are advised to make a practical approach to subject matter in each lesson.